A centenary collection: the Ant Collection of the Museu de Zoologia da Universidade de São Paulo - Ulysséa, Mônica Antunes; Brandão, Carlos R. F. (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2020)
The Formicidae Collection of the Museu de Zoologia da Universidade de São Paulo (MZSP) is an invaluable representation of the ant’s biodiversity, especially from the Neotropical Region. The collection was formed through the contribution of naturalists, authorities in myrmecology, by the results of scientific projects and by virtue of its role as a judicial keeper of ant samples gathered from different scientific studies. In addition to housing a significant number of type material, being 4,741 type specimens of 892 species widely distributed. The constant and adequate curatorial practices necessary for its maintenance and study is one of the major challenges faced by curators. These practices are also a basis for the training of specialized personnel, students and researchers in the biodiversity field. In this work, we present a brief history of the MZSP and a more detailed account of the formation, expansion and qualification of the Formicidae Collection of the MZSP, which currently houses almost 440 thousand pinned specimens, in addition to non-quantified samples in alcohol vials.
Keywords: Biodiversity; Curatorial practice; Entomology; Myrmecology; Scientific collection